(untitled) (Baghdad Science Journal, 2012)
Equilibrium adsorption isotherm for the removal of trifluralin from aqueous solutions using ? –alumina clay has been studied. The result shows that the isotherms were S3 according Giels classification. The effects of various experimental parameters such as contact time, adsorbent dosage, effect of pH and temperature of trifluralin on the adsorption capacities have been investigated. The adsorption isotherms were obtained by obeying freundlich adsorption isotherm with (R2 = 0.91249-0.8149). The thermodynamic parameters have been calculated by using the adsorption process at five different temperature, the values of ?H, ?G and ?S were (_1.0625) kj. mol-1, (7.628 - 7.831) kj.mol-1 and (_2.7966 - _2.9162) kg. k-1. mol-1 respectively. The kinetic study of adsorption process has been studied depending on three kinetic equations: 1- Allergen equation 2- Morris –weber eguation 3- Reichenberg eguation. In general, the result shows the isotherm were on ?- alumina according to Giels classification.? –alumina and thermodynamic